Telaah Epistemologi Pendekatan Irfani Dalam Kajian Hukum Islam - Munawir Saharuddin; Mahsyar Mahsyar (Pusat Riset dan Inovasi Nasional, 2025)
The irfani approach in the study of Islamic law is a method that integrates spiritual experience, intuition, and moral values in understanding and applying legal principles. This research aims to explore the relevance, implications, and challenges of the irfani approach within the context of Islamic law in Indonesia. By employing normative juridical analysis and literature study, this study finds that the irfani approach enriches the understanding of Islamic law by linking it to contemporary issues, such as social justice, environmental protection, and human rights. This perspective encourages a more holistic and ethical interpretation of legal principles, moving beyond rigid textual analysis. Furthermore, this research highlights the potential harmonization between Islamic law and customary law (adat law) in Indonesia. This integration can create a more inclusive, culturally adaptive, and community-responsive legal system, which aligns with Indonesia's pluralistic legal landscape. However, challenges remain in the widespread acceptance and implementation of the irfani approach. Resistance often arises from scholars and institutions that prefer conventional, textual, and rationalistic approaches to Islamic law, perceiving the irfani method as subjective or lacking legal rigor.Despite these challenges, strengthening education, scholarly dialogue, and interdisciplinary engagement between Islamic law scholars, legal practitioners, and policymakers can foster a greater appreciation for the ethical and spiritual dimensions of Islamic law. By incorporating mystical insights and moral considerations, the irfani approach has significant potential to contribute to the evolution of Islamic law in Indonesia, ensuring its relevance, inclusivity, and adaptability in addressing the complex challenges of modern society.